The Psychometric Properties of the of the Torrance test for graphic creative thinking version (A) on a sample of kindergarten children (third category) In the city of Lattakia - ميا, بتول; رنيم أيوب (Latakia University Journal - Arts and Humanities Sciences Series, 2025)
The research aims to study The Psychometric Properties of the of the Torrance test for graphic creative thinking version (A) on a sample of kindergarten children (third category) In the city of Lattakia,Various methods were used to study the validity and reliability of the test.The sample consisted of (150) male and female, and it included (68) boys and (82) girls. The results showed good evidence for the validity of the test by examining the internal consistency, and validity in terms of the extremist groups criterion, in addition to factor analysis. as well as the results showed good indicators of test reliability by verifying the reliability of the scorers and alpha cronbach stability. On this, the research concluded that the Torrance Test for graphic creative Thinking had good Psychometric Properties in the Syrian environment, and its suitable for use in it is within the limits of the research sample.